Industry momentum in Latin America (2023)
We examine whether high-return industries outperform low-return industries in Latin America. Differences in performance between recent winner and loser industries are very often indistinguishable from zero. Evaluating the segment of small and large industries also points us to a lack of return continuation across industries. Employing idiosyncratic returns instead of total returns to differentiate between winner and loser industries confirms that industry momentum does not hold in the region. Furthermore, momentum for individual industries is also absent. Overall, obtaining profits from persistent return differences between or within industries would have been very difficult in our sample period.